PENERAPAN TEKNOLOGI AI GEMINI DALAM PENGEMBANGAN IDE DAN KONSEP VISUAL PADA PEMBELAJARAN KONSENTRASI DKV KELAS XI SMK NEGERI 1 SAMARINDA - Rivaldi Qirom, Januar; Yudha Saputra, Galih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of Artificial Intelligence (AI) Gemini in developing ideas and visual concepts in Visual Communication Design (DKV) learning for grade XI students at SMK Negeri 1 Samarinda. The research used a quantitative approach with a quasi-experimental One Group Pretest–Posttest design involving 35 students. Data were collected through performance tests using pretest and posttest assessments. The results showed that the average pretest score of 71.51 increased to 79.71 in the posttest, indicating an improvement of 8.2 points. This finding indicates that AI Gemini helps students explore ideas and develop visual concepts more effectively. Therefore, AI Gemini can support the learning process in DKV.